2013
DOI: 10.5539/ass.v9n2p298
|View full text |Cite
|
Sign up to set email alerts
|

A Designed Teaching Sequence as a Tool to Improve Students’ Conceptual Understanding of the Conductivity in the Electrolytic Cell

Abstract: This paper reports on a study to determine the efficacy of a teaching sequence following the Leeds model framework designed for a specific content of learning in electrochemistry. The design of the teaching draws upon theoretical insights into perspectives on learning and empirical studies to improve the teaching of this topic, specifically 'Electrolytic Cell'. A case study involving two classes, the Experimental and Baseline classes was carried out for 16-year-old Malaysian upper secondary school students. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(15 reference statements)
0
5
0
Order By: Relevance
“…Contextual learning related to daily life or local context is one of the goals of education for sustainability (UNESCO, 2017; Owens, 2017). However, "electrochemistry is one of the most difficult curriculum domains taught and learned in secondary school chemistry ranked by teachers and students" (Ahmad & Lah, 2013;Eggen, 2010;Supasorn, 2015). The students must deal with complicated reaction and concepts.…”
Section: And Discussionmentioning
confidence: 99%
“…Contextual learning related to daily life or local context is one of the goals of education for sustainability (UNESCO, 2017; Owens, 2017). However, "electrochemistry is one of the most difficult curriculum domains taught and learned in secondary school chemistry ranked by teachers and students" (Ahmad & Lah, 2013;Eggen, 2010;Supasorn, 2015). The students must deal with complicated reaction and concepts.…”
Section: And Discussionmentioning
confidence: 99%
“…Several research studies conducted to cope with identified conceptual difficulties. For example, using cooperative learning instruction (Acar & Tarhan, 2007), conceptual change instruction (Ozkaya, 2002), or use of designed teaching sequence (Ahmad & Lah, 2013). However, no research study proposed a proper instructional model that can be specifically prepared in the context of developing countries like Pakistan.…”
Section: Recommendationsmentioning
confidence: 99%
“…It can be said that the students who followed the normal way of teaching, did not demonstrate good conceptual understanding in the learning areas. This might be because the approaches used in normal classroom teaching did not provide enough support to establish the connections between these three levels of representation by using classroom discourse (although it could also be due to other factors as well) (Ahmad & Lah, 2013). For example, when teaching the nature and properties of electrolytes, if the scientific ideas are presented to the students using the lecture style method without asking them questions, this may lead to students easily forgetting what they had been taught.…”
Section: Discussionmentioning
confidence: 99%